TANTANGAN KOMUNITAS MUSLIM DI INGGRIS PASCA GERAKAN BRITISH EXIT (BREXIT) - Wisnu Pratama, Muhammad Rafi; Yumitro, Gonda; Jha, Gautam Kumar (Jisiera: The Journal of Islamic Studies and International Relations, 2024)
This article discusses the challenges and dynamics faced by the Muslim community in England after the British Exit (Brexit) movement. The implications of Brexit for the Muslim community are very relevant and important to research. In this study, the author analyzes the challenges faced by the Muslim community in England after the Brexit referendum in several main aspects. First, the author examines the political rhetoric associated with Brexit and how it may influence perceptions and attitudes towards Muslims in society. Second, the author evaluates the changing dynamics of Muslim immigration in England and its challenges to the condition of the Muslim community in England. In collecting the data needed for this article, the author conducted a literature study using Harzing, Google Scholar, Taylor & Francis, and other journal sources and trusted website channels. The data analysis method in this article uses qualitative data analysis, where this model analysis is related to data in the form of words or sentences produced from the research object and related to events surrounding a research object. The main findings of this research show that Brexit has presented new challenges and dynamics for the Muslim community in the UK. The political rhetoric associated with Brexit has increased rates of intolerance and discrimination against Muslims in society. In addition, changes in immigration policy that occurred after Brexit had a negative impact on access and stigma for Muslim immigrants.